JP2013189372A - Conductive paste material - Google Patents
Conductive paste material Download PDFInfo
- Publication number
- JP2013189372A JP2013189372A JP2013090284A JP2013090284A JP2013189372A JP 2013189372 A JP2013189372 A JP 2013189372A JP 2013090284 A JP2013090284 A JP 2013090284A JP 2013090284 A JP2013090284 A JP 2013090284A JP 2013189372 A JP2013189372 A JP 2013189372A
- Authority
- JP
- Japan
- Prior art keywords
- conductive paste
- glass
- pbo
- sio
- paste material
- Prior art date
- Legal status (The legal status is an assumption and is not a legal conclusion. Google has not performed a legal analysis and makes no representation as to the accuracy of the status listed.)
- Pending
Links
Classifications
-
- Y—GENERAL TAGGING OF NEW TECHNOLOGICAL DEVELOPMENTS; GENERAL TAGGING OF CROSS-SECTIONAL TECHNOLOGIES SPANNING OVER SEVERAL SECTIONS OF THE IPC; TECHNICAL SUBJECTS COVERED BY FORMER USPC CROSS-REFERENCE ART COLLECTIONS [XRACs] AND DIGESTS
- Y02—TECHNOLOGIES OR APPLICATIONS FOR MITIGATION OR ADAPTATION AGAINST CLIMATE CHANGE
- Y02E—REDUCTION OF GREENHOUSE GAS [GHG] EMISSIONS, RELATED TO ENERGY GENERATION, TRANSMISSION OR DISTRIBUTION
- Y02E10/00—Energy generation through renewable energy sources
- Y02E10/50—Photovoltaic [PV] energy
- Y02E10/546—Polycrystalline silicon PV cells
Landscapes
- Glass Compositions (AREA)
- Photovoltaic Devices (AREA)
- Conductive Materials (AREA)
Abstract
【課題】多結晶Si太陽電池用の導電性ペーストにおいて、高い集電効率を得るために、良好なオーミック接触が得られる導電性ペースト材料が望まれている。
【解決手段】ペーストに含まれる低融点ガラスの組成が、質量%でSiO2を1〜10、B2O3を5〜15、Al2O3を1〜15、PbOを68〜89、CuOを0〜10、TiO2を0〜10含むSiO2−B2O3−Al2O3−PbO系低融点ガラスであることを特徴とする導電性ペースト。前記低融点ガラスの30℃〜300℃における熱膨張係数が(80〜110)×10−7/℃、軟化点が350℃以上500℃以下である特徴も有す。
【選択図】 なしIn order to obtain high current collection efficiency in a conductive paste for polycrystalline Si solar cells, a conductive paste material capable of obtaining good ohmic contact is desired.
The composition of the low melting point glass contained in the paste is, in mass%, 1 to 10, SiO 2 to 5 to 15, B 2 O 3 to 15, Al 2 O 3 to 15, PbO to 68 to 89, CuO. Is a SiO 2 —B 2 O 3 —Al 2 O 3 —PbO-based low-melting glass containing 0 to 10 and TiO 2 from 0 to 10. The low-melting glass has a feature that the thermal expansion coefficient at 30 ° C. to 300 ° C. is (80 to 110) × 10 −7 / ° C., and the softening point is 350 ° C. or more and 500 ° C. or less.
[Selection figure] None
Description
本発明は、特に多結晶Si太陽電池に形成される受光面電極において、良好なオーミック接触が得られる導電性ペースト材料を用いた太陽電池に関する。 The present invention relates to a solar cell using a conductive paste material that can provide good ohmic contact, particularly in a light-receiving surface electrode formed in a polycrystalline Si solar cell.
従来、多結晶Si太陽電池はp型シリコン基板の一方の面にn型シリコン基板層を設けた構造となっており、そのn型シリコン層側を受光面とし、受光面側表面に受光効率をあげるための窒化珪素膜などの反射防止膜を設け、さらにその反射防止膜側に半導体と接続した表面電極と、その裏面に裏面電極を設けることで受光により半導体のpn接合に生じた電力を取り出していた。 Conventionally, a polycrystalline Si solar cell has a structure in which an n-type silicon substrate layer is provided on one surface of a p-type silicon substrate. The n-type silicon layer side is used as a light-receiving surface, and light-receiving efficiency is provided on the surface of the light-receiving surface. An antireflection film, such as a silicon nitride film, is provided, and a surface electrode connected to the semiconductor is provided on the antireflection film side, and a back electrode is provided on the back surface, thereby taking out the power generated in the pn junction of the semiconductor by light reception It was.
このとき、表面電極を形成する場合、受光効率をあげるために形成された窒化珪素膜などの反射防止膜が比較的高い電気抵抗値を持つことから、これら反射防止膜をあらかじめエッチングし、そこへ導電性ペーストなどの電極材料を印刷・焼成することで半導体と電極とを接続していた。 At this time, when the surface electrode is formed, the antireflection film such as a silicon nitride film formed for increasing the light receiving efficiency has a relatively high electric resistance value. The semiconductor and the electrode are connected by printing and baking an electrode material such as a conductive paste.
しかしこのようなエッチングによる方法は工程増によるコストアップなどの理由から、このようなエッチングは行わず、電極材料を直接反射防止膜上に印刷・焼成することで同時に反射防止膜を熔融・除去し電極と半導体とを接続する方法がとられるようになってきた。このとき、表面電極材料の導電性ペーストにリン等の周期表第V族に属する元素を含有したり(特許文献1参照)、Ti、Bi、Co、Zn、Zr、Fe、Cr成分を含有したり(特許文献2参照)、様々な添加剤を種々配合し高いオーミック接触を得ようとする方法が提案されている。
しかしながら、上記のように表面電極材料に種々金属を含有する添加剤を配合して焼成した場合、半導体と表面電極の間に安定したオーミック接触をえることができなかった。 However, when an additive containing various metals is blended in the surface electrode material as described above, stable ohmic contact cannot be obtained between the semiconductor and the surface electrode.
そこで本発明は、上述の問題点を解決すべくなされたもので、反射防止膜をファイアースルーして半導体基板と表面電極との良好なオーミック接触をえることのできる導電性ペーストを用いた多結晶Si太陽電池を提供することにある。 Accordingly, the present invention has been made to solve the above-mentioned problems, and uses a conductive paste that can fire through the antireflection film to obtain a good ohmic contact between the semiconductor substrate and the surface electrode. The object is to provide a Si solar cell.
本発明は、p型シリコン基板の一方の面に受光面となるn型シリコン基板層を設け、該受光面側表面に設けた反射防止膜上に導電性ペーストを印刷・焼成することで同時に反射防止膜を熔融・除去して表面電極が形成されている多結晶Si太陽電池において、該ペーストに含まれる低融点ガラスの組成が、質量%でSiO2 1〜10、B2O3 5〜15、Al2O3 1〜15、PbO 68〜89、CuO 0〜10、TiO2 0〜10含むSiO2−B2O3−Al2O3−PbO系低融点ガラスであり、該表面電極とp型シリコン基板面に形成されたn型シリコン半導体とがオーミック接触していることを特徴とする。 In the present invention, an n-type silicon substrate layer serving as a light-receiving surface is provided on one surface of a p-type silicon substrate, and a conductive paste is printed and baked on an anti-reflection film provided on the light-receiving surface-side surface. In the polycrystalline Si solar cell in which the surface electrode is formed by melting and removing the protective film, the composition of the low melting point glass contained in the paste is SiO 2 1 to 10 and B 2 O 3 5 to 15 by mass%. , Al 2 O 3 1-15, PbO 68-89, CuO 0-10, TiO 2 0-10 containing SiO 2 —B 2 O 3 —Al 2 O 3 —PbO based low melting point glass, The n-type silicon semiconductor formed on the p-type silicon substrate surface is in ohmic contact.
また、前記低融点ガラスの30℃〜300℃における熱膨張係数が(80〜110)×10−7/℃、軟化点が350℃以上500℃以下であることを特徴とする。 The low-melting-point glass has a thermal expansion coefficient of 30 to 300 ° C. (80 to 110) × 10 −7 / ° C. and a softening point of 350 to 500 ° C.
さらに、上記の導電性ペーストを使用することを特徴とする電子材料用基板である。 Furthermore, it is an electronic material substrate characterized by using the above conductive paste.
本発明はp型シリコン基板の一方の面に受光面となるn型シリコン基板層を設け、該受光面側表面に設けた反射防止膜上に導電性ペーストを印刷・焼成することで同時に反射防止膜を熔融・除去して表面電極が形成されている多結晶Si太陽電池であり、該表面電極とp型シリコン基板面に形成されたn型シリコン半導体とがオーミック接触しているものである。 In the present invention, an n-type silicon substrate layer serving as a light-receiving surface is provided on one surface of a p-type silicon substrate, and a conductive paste is printed and fired on the anti-reflection film provided on the light-receiving surface side surface, thereby simultaneously preventing reflection. A polycrystalline Si solar cell in which a surface electrode is formed by melting and removing the film, and the surface electrode and an n-type silicon semiconductor formed on the p-type silicon substrate surface are in ohmic contact.
また、前記低融点ガラスの30℃〜300℃における熱膨張係数が(80〜110)×10−7/℃、軟化点が350℃以上500℃以下であることを特徴とする。 The low-melting-point glass has a thermal expansion coefficient of 30 to 300 ° C. (80 to 110) × 10 −7 / ° C. and a softening point of 350 to 500 ° C.
さらに、上記の導電性ペーストを使用することを特徴とする電子材料用基板である。 Furthermore, it is an electronic material substrate characterized by using the above conductive paste.
SiO2はガラス形成成分であり、別のガラス形成成分であるB2O3と共存させることにより、安定したガラスを形成することができるもので、質量%で1〜10%の範囲で含有させる。10%を越えると、ガラスの軟化点が上昇し、成形性、作業性が困難となる。より好ましくは、4〜7%の範囲である。 SiO 2 is a glass forming component, and can coexist with B 2 O 3 which is another glass forming component to form a stable glass. It is contained in a range of 1 to 10% by mass%. . If it exceeds 10%, the softening point of the glass will increase, making the formability and workability difficult. More preferably, it is 4 to 7% of range.
B2O3はガラス形成成分であり、ガラス溶融を容易とし、ガラスの熱膨張係数において過度の上昇を抑え、かつ、焼付け時にガラスに適度の流動性を与え、ガラスの誘電率を低下させるものである。ガラス中に5〜15%(質量%、以下においても同様である)の範囲で含有させるのが好ましい。2%未満ではガラスの流動性が不充分となり、焼結性が損なわれる。他方15%を越えるとガラスの安定性を低下させる。より好ましくは8〜12%の範囲である。 B 2 O 3 is a glass-forming component, facilitates glass melting, suppresses an excessive increase in the coefficient of thermal expansion of glass, gives moderate fluidity to glass during baking, and lowers the dielectric constant of glass It is. It is preferable to make it contain in 5 to 15% (mass%, it is the same also in the following) in glass. If it is less than 2%, the fluidity of the glass becomes insufficient, and the sinterability is impaired. On the other hand, if it exceeds 15%, the stability of the glass is lowered. More preferably, it is 8 to 12% of range.
Al2O3はガラスを安定化させ、またその導入により半導体と表面電極とのオーミック接触を上げる効果を持つ。ガラス中に1〜15%の範囲で含有させることが好ましい。1未満では上記作用を発揮しえず、15%を超えるとガラスが不安定となる。より好ましくは3〜10%の範囲である。 Al 2 O 3 has the effect of stabilizing the glass and increasing the ohmic contact between the semiconductor and the surface electrode. It is preferable to make it contain in 1 to 15% of range in glass. If it is less than 1, the above action cannot be exhibited, and if it exceeds 15%, the glass becomes unstable. More preferably, it is 3 to 10% of range.
PbOはガラスを低融点化し、流動性を与え、反射防止膜をファイアースルーし半導体と表面電極との接触面を大きくする効果を持つ成分である。ガラス中に68〜89%で含有させるのが好ましい。68%未満ではその作用を発揮し得ず、他方89%を超えると熱膨張係数が過大となる。より好ましくは75〜85%である。 PbO is a component that has the effect of lowering the melting point of glass, imparting fluidity, fire-through the antireflection film, and increasing the contact surface between the semiconductor and the surface electrode. It is preferable to make it contain at 68 to 89% in glass. If it is less than 68%, the effect cannot be exhibited. On the other hand, if it exceeds 89%, the thermal expansion coefficient becomes excessive. More preferably, it is 75 to 85%.
CuOはその導入により半導体と表面電極とのオーミック接触を上げる効果があり、0〜10%の範囲で含有させるのが好ましい。10%を超えると熔融時においてガラスが結晶化しやすくなる。より好ましくは0〜5%である。 The introduction of CuO has an effect of increasing the ohmic contact between the semiconductor and the surface electrode, and it is preferably contained in the range of 0 to 10%. If it exceeds 10%, the glass tends to crystallize during melting. More preferably, it is 0 to 5%.
TiO2はその導入により半導体と表面電極とのオーミック接触を上げる効果があり、0〜10%の範囲で含有させるのが好ましい。10%を超えると熔融時においてガラスが結晶化しやすくなる。より好ましくは0〜5%である。 The introduction of TiO 2 has the effect of increasing the ohmic contact between the semiconductor and the surface electrode, and it is preferably contained in the range of 0 to 10%. If it exceeds 10%, the glass tends to crystallize during melting. More preferably, it is 0 to 5%.
この他にも、一般的な酸化物で表すRO(MgO、CaO、SrO、BaO)、R2O(Li2O、Na2O、K2O)、In2O3、Bi2O3、SnO2、TeO2などを加えてもよい。 In addition to this, RO (MgO, CaO, SrO, BaO), R 2 O (Li 2 O, Na 2 O, K 2 O), In 2 O 3 , Bi 2 O 3 , which are represented by general oxides, SnO 2 , TeO 2 or the like may be added.
30℃〜300℃における熱膨張係数が(80〜110)×10−7/℃、軟化点が350℃以上500℃以下である上記の無鉛低融点ガラスを導電性ペーストに含有させ、多結晶Si太陽電池に用いる。熱膨張係数が(80〜110)×10−7/℃を外れると表面電極形成時に剥離、基板の反り等の問題が発生する。好ましくは、(85〜110)×10−7/℃の範囲である。また、軟化点が500℃を越えると基板の軟化変形などの問題が発生する。好ましくは、360℃以上490℃以下である。 The lead-free low-melting glass having a thermal expansion coefficient at 30 ° C. to 300 ° C. of (80 to 110) × 10 −7 / ° C. and a softening point of 350 ° C. or higher and 500 ° C. or lower is contained in a conductive paste, and polycrystalline Si Used for solar cells. When the thermal expansion coefficient is outside (80 to 110) × 10 −7 / ° C., problems such as peeling and warping of the substrate occur when the surface electrode is formed. Preferably, it is in the range of (85 to 110) × 10 −7 / ° C. If the softening point exceeds 500 ° C., problems such as softening deformation of the substrate occur. Preferably, they are 360 degreeC or more and 490 degrees C or less.
以下、実施例に基づき、説明する。 Hereinafter, a description will be given based on examples.
(導電性ペースト材料)
まず、ガラス粉末は、実施例に記載した所定組成となるように各種無機原料を秤量、混合して原料バッチを作製する。この原料バッチを白金ルツボに投入し、電気加熱炉内で1000〜1300℃、1〜2時間で加熱溶融して表1の実施例1〜5、表2の比較例1〜4に示す組成のガラスを得た。
(Conductive paste material)
First, various inorganic raw materials are weighed and mixed so that the glass powder has a predetermined composition described in the examples to prepare a raw material batch. The raw material batch was put into a platinum crucible and heated and melted in an electric heating furnace at 1000 to 1300 ° C. for 1 to 2 hours. The compositions shown in Examples 1 to 5 in Table 1 and Comparative Examples 1 to 4 in Table 2 were used. Glass was obtained.
ガラスの一部は型に流し込み、ブロック状にして熱物性(熱膨張係数、軟化点)測定用に供した。残余のガラスは急冷双ロール成形機にてフレーク状とし、粉砕装置で平均粒径1〜4μm、最大粒径10μm未満の粉末状に整粒した。 A part of the glass was poured into a mold, made into a block shape, and used for measurement of thermal properties (thermal expansion coefficient, softening point). The remaining glass was made into flakes with a rapid cooling twin roll molding machine, and sized with a pulverizer into a powder having an average particle size of 1 to 4 μm and a maximum particle size of less than 10 μm.
次いで、αテルピネオールとブチルカルビトールアセテートからなるペーストオイルにバインダーとしてのエチルセルロースと上記ガラス粉、また導電性粉末として銀粉末を所定比で混合し、粘度、500±50ポイズ程度の導電性ペーストを調製した。 Next, a paste oil composed of α-terpineol and butyl carbitol acetate is mixed with ethyl cellulose as a binder and the above glass powder and silver powder as a conductive powder at a predetermined ratio to prepare a conductive paste having a viscosity of about 500 ± 50 poise. did.
なお、軟化点は、リトルトン粘度計を用い、粘度係数η=107.6 に達したときの温度とした。また、熱膨張係数は、熱膨張計を用い、5℃/分で昇温したときの30〜300℃での伸び量から求めた。 The softening point was the temperature when the viscosity coefficient η = 10 7.6 was reached using a Littleton viscometer. Moreover, the thermal expansion coefficient was calculated | required from the amount of elongation at 30-300 degreeC when it heated up at 5 degree-C / min using the thermal dilatometer.
次に、表面に窒化珪素層、また裏面にアルミ電極層が形成された1辺30mmの多結晶シリコンを準備し、その窒化珪素層上部に上記で作製した導電性ペーストをスクリーン印刷した。これらの試験片を、140℃のオーブンで10分間乾燥させ、次に電気炉で800℃条件下で焼成し、サンプルを得た。 Next, polycrystalline silicon having a side of 30 mm with a silicon nitride layer formed on the front surface and an aluminum electrode layer formed on the back surface was prepared, and the conductive paste prepared above was screen-printed on the silicon nitride layer. These test pieces were dried in an oven at 140 ° C. for 10 minutes, and then baked in an electric furnace at 800 ° C. to obtain a sample.
このようにして得られたデバイスについて、太陽電池としての集電効率(0〜1.0)を測定し、その効率が0.7以上のものを○、0.7未満のものを×とした。 About the device obtained in this way, the current collection efficiency (0-1.0) as a solar cell was measured, the thing whose efficiency is 0.7 or more was made into (circle), and the thing less than 0.7 was made into x. .
(結果)
低融点ガラス組成および、各種試験結果を表に示す。
(result)
The low melting point glass composition and various test results are shown in the table.
表1における実施例1〜5に示すように、本発明の多結晶Si太陽電池に用いる低融点ガラスの組成範囲内においては、軟化点が350℃〜500℃であり、好適な熱膨張係数(80〜110)×10−7/℃を有しており、更には、集電効率が0.7以上と良好であり、多結晶Si太陽電池用として好適である。 As shown in Examples 1 to 5 in Table 1, the softening point is 350 ° C. to 500 ° C. within the composition range of the low-melting glass used for the polycrystalline Si solar cell of the present invention. 80 to 110) × 10 −7 / ° C. Furthermore, the current collection efficiency is as good as 0.7 or more, and it is suitable for a polycrystalline Si solar cell.
他方、上記組成範囲を外れる表2における比較例1〜4は、良好な集電特性が得られない、または熔融時に結晶化するなど、多結晶Si太陽電池として適用し得ない。 On the other hand, Comparative Examples 1 to 4 in Table 2 outside the above composition range cannot be applied as a polycrystalline Si solar cell because good current collection characteristics cannot be obtained or crystallization occurs during melting.
Claims (4)
SiO2 1〜10、
B2O3 5〜15、
Al2O3 1〜15、
PbO 68〜89、
CuO 0(ただし、0を含まず)〜5、
TiO2 0〜10であるSiO2−B2O3−Al2O3−PbO−CuO系ガラスであることを特徴とする導電性ペースト材料。 The composition of the low melting point glass having a thermal expansion coefficient of (80 to 110) × 10 −7 / ° C. and a softening point of 350 ° C. or more and 500 ° C. or less contained in the conductive paste at 30% to 300 ° C. is SiO. 2 1-10,
B 2 O 3 5-15,
Al 2 O 3 1-15,
PbO 68-89,
CuO 0 (but not including 0) to 5,
A conductive paste material, which is SiO 2 —B 2 O 3 —Al 2 O 3 —PbO—CuO-based glass that is TiO 2 0 to 10.
SiO2 1〜10、
B2O3 5〜15、
Al2O3 3〜10、
PbO 68〜89、
CuO 0〜10、
TiO2 0〜10であるSiO2−B2O3−Al2O3−PbO系ガラスであることを特徴とする導電性ペースト材料。 The composition of the low melting point glass having a thermal expansion coefficient of (80 to 110) × 10 −7 / ° C. and a softening point of 350 ° C. or more and 500 ° C. or less contained in the conductive paste at 30% to 300 ° C. is SiO. 2 1-10,
B 2 O 3 5-15,
Al 2 O 3 3-10,
PbO 68-89,
CuO 0-10,
A conductive paste material, which is SiO 2 —B 2 O 3 —Al 2 O 3 —PbO-based glass that is TiO 2 to 10.
Priority Applications (1)
| Application Number | Priority Date | Filing Date | Title |
|---|---|---|---|
| JP2013090284A JP2013189372A (en) | 2013-04-23 | 2013-04-23 | Conductive paste material |
Applications Claiming Priority (1)
| Application Number | Priority Date | Filing Date | Title |
|---|---|---|---|
| JP2013090284A JP2013189372A (en) | 2013-04-23 | 2013-04-23 | Conductive paste material |
Related Parent Applications (1)
| Application Number | Title | Priority Date | Filing Date |
|---|---|---|---|
| JP2007270154A Division JP5272373B2 (en) | 2007-10-17 | 2007-10-17 | Polycrystalline Si solar cell |
Publications (1)
| Publication Number | Publication Date |
|---|---|
| JP2013189372A true JP2013189372A (en) | 2013-09-26 |
Family
ID=49390047
Family Applications (1)
| Application Number | Title | Priority Date | Filing Date |
|---|---|---|---|
| JP2013090284A Pending JP2013189372A (en) | 2013-04-23 | 2013-04-23 | Conductive paste material |
Country Status (1)
| Country | Link |
|---|---|
| JP (1) | JP2013189372A (en) |
Cited By (1)
| Publication number | Priority date | Publication date | Assignee | Title |
|---|---|---|---|---|
| WO2015115747A1 (en) * | 2014-01-28 | 2015-08-06 | 주식회사 동진쎄미켐 | Glass composition and electrode composition for solar cell using same |
Citations (10)
| Publication number | Priority date | Publication date | Assignee | Title |
|---|---|---|---|---|
| JPS59195552A (en) * | 1983-04-20 | 1984-11-06 | Matsushita Electric Ind Co Ltd | Glass composition for coating and glass paste for coating |
| JPS615406A (en) * | 1985-05-30 | 1986-01-11 | Hitachi Ltd | Composit-type magnetic head |
| JPS61227940A (en) * | 1985-03-29 | 1986-10-11 | Sumitomo Metal Mining Co Ltd | Glass paste |
| JPS6249676A (en) * | 1985-08-29 | 1987-03-04 | Sharp Corp | Solar battery |
| JPH06135736A (en) * | 1990-12-17 | 1994-05-17 | Hitachi Metals Ltd | Bonding glass for composite type magnetic head assembly and magnetic head |
| JPH087645A (en) * | 1994-06-20 | 1996-01-12 | Murata Mfg Co Ltd | Conductive paste and multilayer ceramic capacitor |
| JPH11228168A (en) * | 1998-02-06 | 1999-08-24 | Nippon Electric Glass Co Ltd | Low melting point glass for magnetic head |
| JP2001039734A (en) * | 1999-07-23 | 2001-02-13 | Central Glass Co Ltd | Low melting point glass for formation of transparent insulating coating film |
| JP2006351530A (en) * | 2005-06-07 | 2006-12-28 | E I Du Pont De Nemours & Co | Aluminum thick film composition, electrode, semiconductor device and method for producing them |
| JP2009099781A (en) * | 2007-10-17 | 2009-05-07 | Central Glass Co Ltd | Conductive paste material |
-
2013
- 2013-04-23 JP JP2013090284A patent/JP2013189372A/en active Pending
Patent Citations (10)
| Publication number | Priority date | Publication date | Assignee | Title |
|---|---|---|---|---|
| JPS59195552A (en) * | 1983-04-20 | 1984-11-06 | Matsushita Electric Ind Co Ltd | Glass composition for coating and glass paste for coating |
| JPS61227940A (en) * | 1985-03-29 | 1986-10-11 | Sumitomo Metal Mining Co Ltd | Glass paste |
| JPS615406A (en) * | 1985-05-30 | 1986-01-11 | Hitachi Ltd | Composit-type magnetic head |
| JPS6249676A (en) * | 1985-08-29 | 1987-03-04 | Sharp Corp | Solar battery |
| JPH06135736A (en) * | 1990-12-17 | 1994-05-17 | Hitachi Metals Ltd | Bonding glass for composite type magnetic head assembly and magnetic head |
| JPH087645A (en) * | 1994-06-20 | 1996-01-12 | Murata Mfg Co Ltd | Conductive paste and multilayer ceramic capacitor |
| JPH11228168A (en) * | 1998-02-06 | 1999-08-24 | Nippon Electric Glass Co Ltd | Low melting point glass for magnetic head |
| JP2001039734A (en) * | 1999-07-23 | 2001-02-13 | Central Glass Co Ltd | Low melting point glass for formation of transparent insulating coating film |
| JP2006351530A (en) * | 2005-06-07 | 2006-12-28 | E I Du Pont De Nemours & Co | Aluminum thick film composition, electrode, semiconductor device and method for producing them |
| JP2009099781A (en) * | 2007-10-17 | 2009-05-07 | Central Glass Co Ltd | Conductive paste material |
Non-Patent Citations (1)
| Title |
|---|
| JPN6014036389; I.W.DONALD: 'Preparation, properties and chemistry of glass- and glass-ceramic-to-metal seals and coatings' Journal of Materials Science Vol.28, No.11, 19930601, Page.2841-2886, Springer * |
Cited By (1)
| Publication number | Priority date | Publication date | Assignee | Title |
|---|---|---|---|---|
| WO2015115747A1 (en) * | 2014-01-28 | 2015-08-06 | 주식회사 동진쎄미켐 | Glass composition and electrode composition for solar cell using same |
Similar Documents
| Publication | Publication Date | Title |
|---|---|---|
| JP5272373B2 (en) | Polycrystalline Si solar cell | |
| JP5888493B2 (en) | Conductive paste and solar cell element using the conductive paste | |
| JP5609319B2 (en) | Low melting point glass composition and conductive paste material using the same | |
| JP6531421B2 (en) | Bi2O3-TeO2-SiO2-WO3-RO Glass | |
| JPWO2009041182A1 (en) | Ag electrode paste, solar battery cell and manufacturing method thereof | |
| CN101809678A (en) | Conductive compositions and processes for use in the manufacture of semiconductor devices | |
| JP6142756B2 (en) | Glass powder material | |
| JP2006351530A (en) | Aluminum thick film composition, electrode, semiconductor device and method for producing them | |
| JP5569094B2 (en) | Low melting point glass composition and conductive paste material using the same | |
| KR101474677B1 (en) | Conductive paste and solar battery cell using said conductive paste | |
| TW201332926A (en) | Glass for electrode formation and electrode forming material using the same | |
| WO2012111478A1 (en) | Conductive paste and solar cell | |
| JP2012066993A (en) | Glass for electrode formation and electrode formation material using the same | |
| JP5796281B2 (en) | Electrode forming material | |
| JP2014005162A (en) | Glass for electrode formation and electrode formation material using the same | |
| JP2014028713A (en) | Glass for electrode formation and electrode formation material using the same | |
| JP2014105153A (en) | Bismuth-based glass composition and electrode formation material using the same | |
| JP2013212949A (en) | Glass for electrode formation and electrode forming material using the same |
Legal Events
| Date | Code | Title | Description |
|---|---|---|---|
| A977 | Report on retrieval |
Free format text: JAPANESE INTERMEDIATE CODE: A971007 Effective date: 20140724 |
|
| A131 | Notification of reasons for refusal |
Free format text: JAPANESE INTERMEDIATE CODE: A131 Effective date: 20140826 |
|
| A02 | Decision of refusal |
Free format text: JAPANESE INTERMEDIATE CODE: A02 Effective date: 20150203 |
